Muito mais que mel: uma análise dos padrões funcionais de polinizadores em diferentes ecossistemas - Capitani, Luana Camila (2024)
Pollination, among ecosystem services, is probably the most critically impacted, being considered the biggest global crisis on biodiversity. However, we still know little about the dynamics of plant-pollinator relationships between natural ecosystems and new ecosystems, formed by mosaics of native areas and productive matrix, with different scales of anthropic pressure. In this study, through mixed linear models and plant-pollinator interaction networks, we investigate the influence of variables related to the type (city, crop, pasture and native) and landscape quality (characteristics and conservation status of ecosystems), and habitat variables (temperature, relative humidity, wind speed and number of available flowers) on plant-pollinator systems. Focusing on changes in ecosystem functionality, related to the quality of floral resources offered, and the composition and functional roles of pollinators, using as a case study Bauhinia forficata Link floral visitor’s guild. The results indicate that pasture areas are closer to native areas, and that crop and city areas require special attention regarding the functionality of the pollination ecosystem service. There is also evidence that degraded ecosystems differ from natural and conserved areas in terms of the quality of the resources offered and the functional roles played by pollinators, even if the species composition is similar. B. forficata actively responds to the conservation status of ecosystems, increasing the supply of floral resources in degraded areas or areas with lower species abundance (positive feedback). With adaptive maximum transposed into crop areas, due to competition with crops. The greater the local attractiveness of the plant, whether in terms of quality or quantity of resources, the greater the potential for maintaining key pollinator species. Some functional groups of floral visitors are indicators of environmental quality, with emphasis on Lepidoptera in altered and impacted areas and Hymenoptera in natural areas. Species with aggressive behavior adapt to more hostile environments, and condition other species to use marginal resources. The tendency in degraded ecosystems is generalist’s species in terms of habitat and behavior, with functional roles that are distinct from those they play in natural areas. The arrangement, composition, and functional roles of species respond to landscape and habitat variables through functional adaptations in generalist species, rather than through specialization process. And finally, the type of landscape and conservation status select which species/groups of pollinators can occur, and the habitat variables select, among the possible species, which ones will be present at the time, and how they will behave.